Recent advances in IoT, edge computing and its applications - Gunawan, Teddy Surya (2020)
Internet of Things (IoT) is one of the critical enablers of the Industrial Revolution 4.0. IoT can be used in many applications that require precision, such as agriculture, industrial automation, education, automotive, and smart cities, to name a few. On the other hand, edge computing is gaining popularity in recent years as it creates new and improved ways to maximize operational efficiency, improve performance and privacy, and ensure “always-on” availability. Edge computing is a form of distributed computing model in which the computing takes place near the physical location where data is being collected, rather than on a centralized server or in the cloud. The objective of this talk is to discuss the recent advances in IoT, edge computing and its applications. First, the IoT developer survey 2020 will be highlighted. Then, the IoT framework will be introduced to solve a complex problem, including Things, Connect, Collect, Learn, and Do. Finally, various examples of applications using IoT and edge computing to tackle pandemic and beyond pandemic will be presented. Finally, due to the current world situation, national technology resilience is now a necessity rather than necessary. Future direction to enhance national technology resilience will be elaborated.